2018
DOI: 10.2147/rmhp.s154611
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health risk of working in garages: comparative study on blood pressure and hematological parameters between garage workers and Haramaya University community, Harar, eastern Ethiopia

Abstract: BackgroundOccupational exposure to chemicals in garages causes a wide range of biological effects, depending upon the level and duration of exposure. In Ethiopia, there have been few studies conducted to assess the exposure of garage workers to chemicals. Preceding studies have not explored the effect of working in garage on blood pressure and hematological parameters. Therefore, this study aimed to assess differences in blood pressure and hematological parameters among garage workers compared to the Haramaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
1
22
1
Order By: Relevance
“…Most garage workers do not use protective equipment while handling the used engine oil, also they do not change their cloth after coming in contact with the used oil, thus increasing their chance of contact with the used oil. In Ethiopia, majority of the workers (80%) do not use any kind of personal protective equipment and did not follow safety measures [5]. According to the same study, 46.67% of garage workers had a habit of smoking, drinking, and eating at the garage where the used oil is kept, further increasing their chance of ingesting the used oil.…”
Section: Awareness Of Garage Workers On the Impacts Of Used Engine Oimentioning
confidence: 99%
See 2 more Smart Citations
“…Most garage workers do not use protective equipment while handling the used engine oil, also they do not change their cloth after coming in contact with the used oil, thus increasing their chance of contact with the used oil. In Ethiopia, majority of the workers (80%) do not use any kind of personal protective equipment and did not follow safety measures [5]. According to the same study, 46.67% of garage workers had a habit of smoking, drinking, and eating at the garage where the used oil is kept, further increasing their chance of ingesting the used oil.…”
Section: Awareness Of Garage Workers On the Impacts Of Used Engine Oimentioning
confidence: 99%
“…This was explained to be caused by the high rate of unemployment. Also in Ethiopia, the majority (43%) of garage workers were found to be about 28-37 years old [5]. Poor education among the auto and motor garage workers in Ouagadougou could be due to the availability of a number of casual jobs that do not necessitate any formal education.…”
Section: Effect Of Farmers' Age and Educational Levels On Management mentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Our previous work indicates that there were significant differences in blood pressure and hematological parameters between garage workers and the control group. 25 However, to the best of the investigators’ knowledge, data are lacking on the effects of different types of chemical exposure at the workplace on biochemical levels. Therefore, the aim of this study was to describe the level of biochemical levels and determine their differences among garage workers compared with the nonexposed control individuals in Harar town.…”
Section: Introductionmentioning
confidence: 99%
“…Apreko et al (2015) suggested that a good ambience in an automotive garage is achieved through good housekeeping, lighting, ventilation, maintenance of the floor and drainage as well as washroom facilities. Ataro et al (2018) made a shocking revelation that the safety in automobile garage is always sabotaged by poor working environment. Substantiating the above fact, the surveys conducted at several garages in India have revealed that the ambience was found to be very poor in several freelances and depot garages, which was not congenial for the technicians.…”
Section: Challenges Of Automobile Maintenance Service Garagesmentioning
confidence: 99%